Informing future research priorities into the psychological and social problems faced by cancer survivors: a rapid review and synthesis of the literature. - Jarrett, N; Scott, I; Addington-Hall, J; Amir, Z; Brearley, S; Hodges, L; Richardson, A; Sharpe, M; Stamataki, Z; Stark, D; Siller, C; Ziegler, L; et al. (2013)
PURPOSE: To establish what is known regarding the psychological and social problems faced by adult cancer survivors (people who are living with and beyond a diagnosis of cancer) and identify areas future research should address. METHOD: A rapid search of published literature reviews held in electronic data bases was under taken. Inclusion and exclusion criteria, and removal of duplicated papers, reduced the initial number of papers from 4051 to 38. Twenty-two review papers were excluded on grounds of quality and 16 review papers were selected for appraisal. RESULTS: The psychological and social problems for cancer survivors are identified as depression, anxiety, distress, fear of recurrence, social support/function, relationships and impact on family, and quality of life. A substantial minority of people surviving cancer experience depression, anxiety, and distress or fear associated with recurrence or follow up. There is some indication that social support is positively associated with better outcomes. Quality of life for survivors of cancer appears generally good for most people, but an important minority experience a reduction in quality of life, especially those with more advanced disease and reduced social and economic resources. The majority of research knowledge is based on women with breast cancer. The longer term implications of cancer survival have not been adequately explored. CONCLUSIONS: Focussing well designed research in the identified areas where less is already known about the psychological and social impact of cancer survival is likely to have the greatest impact on the wellbeing of people surviving cancer.